THE INFLUENCE OF BRAND AUTHENTICITY, BRAND SELF-CONGRUENCE, AND BRAND LOVE TOWARDS BRAND ENGAGEMENT OF TOURIST DESTINATION IN WEST SUMATERA (JURNAL ECONOMICA : Research of Economic And Economic Education, 2022)
This study aims to analyse the effect of brand authentic, brand self-congruence, and brand love on brand engagement of tourist destinations in West Sumatra. The research population is all tourists who have visited West Sumatra tourist destinations in the last 5 years. The sample was collected using a simple random sampling technique and the questionnaire distributed to 585 respondents. The data analysis technique used is multiple regression analysis. The results showed that (1) brand authenticity had a positive and significant effect on destination brand engagement. (2) brand self-congruence has a positive and significant effect on destination brand engagement, (3) brand love has a positive and significant effect on destination brand engagement.